Bridging the loneliness gap: Interventions to address social isolation and mental health in older adults - Mohd Yusof, Noorlailahusna; Mat Yasin, Suziana (Journal of Islamic, Social, Economics and Development, 2025)
This study addresses the critical issue of social isolation and its adverse impact on the mental health of older adults. With global aging trends intensifying, the research aims to assess the effectiveness of community engagement programs and combined physical activity and social interaction interventions in reducing loneliness and enhancing mental well-being. The study employs a systematic review of peer-reviewed articles, reports, and books using the Scopus database with a structured keyword search. Literature synthesis is used to provide contextual depth, integrating insights from social, psychological, and physical health perspectives. A conceptual framework is proposed, highlighting the interconnections between social isolation, mental health challenges, and effective interventions. Findings indicate that community engagement programs foster regular social interactions, emotional support, and a sense of purpose, significantly reducing loneliness and anxiety. Physical activity interventions, particularly group-based activities like walking clubs and dance programs, enhance mobility and social connectedness, contributing to improved cognitive function and mental well-being. Technological innovations, including telehealth services, AI-driven tools, and online social networking platforms, provide accessible solutions for socially isolated individuals, especially those with mobility constraints. These interventions collectively address the multifaceted nature of isolation by enhancing social connectedness and self-efficacy. The study highlights the need for multi-faceted, scalable, and culturally sensitive strategies to combat social isolation among older adults. By integrating community-based programs, physical activities, and technology, stakeholders can create age-friendly environments that reduce loneliness and improve mental health. The findings reinforce the importance of inclusive policies, digital literacy initiatives, and cross-sector collaboration in fostering social inclusion. Future research should focus on longitudinal studies to explore long-term impacts and on participatory approaches to design interventions aligned with older adults' needs.